Mobile technology, games and nature areas: The tourist perspective - Marcelo de Oliveira Nunes; Verônica Feder Mayer (Tourism & Management Studies)
New mobile technologies such as smartphones and tablets allow tourists and tourism service providers to interact nearly free of time or space constraints. Since tourists are by definition mobile, it is argued that this trend merits greater focus in research involving the various spaces through which “the always connected traveller” passes. Hence, this study aims to test the acceptance of a smartphone game which would support the tourism experience of visitors to an island with tourism. To this end, a survey was carried out with 378 tourists who perceived using the game as useful, easy, enjoyable, and compatible with the location. Results indicate that an updated tourist profile of a more connected and technologically sophisticated public includes interest in interaction with mobile technologies that assist tourists even on trips where they want to experience nature, adventure, social interaction and relaxation. Finally, the authors reflect on the use of games as a means of promoting sustainable behaviour among tourists.